2021
DOI: 10.1177/0033688220981784
|View full text |Cite
|
Sign up to set email alerts
|

Language Teaching during a Pandemic: A Case Study of Zoom Use by a Secondary ESL Teacher in Hong Kong

Abstract: This article reports a case study of an English as a Second Language (ESL) teacher in Hong Kong who conducted lessons via Zoom during the COVID-19 pandemic. The study focused on the factors influencing her technology integration in synchronous online teaching mode. Using data from classroom recordings, stimulated-recall and semi-structured interviews, this study uncovered how Zoom functioned as a substitute for face-to-face lessons. The findings revealed that although there were fewer interactions between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 49 publications
7
89
1
6
Order By: Relevance
“…The data in Table 2 revealed that EFL learners have positive attitudes toward the use of social media in language learning, which is in line with the previous research with regard to the use of social media in general (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019;Bailey, Park, & Haji, 2017;Balbay, & Kilis, 2017;Eaton, 2010;Elia, 2006;Fewell, 2014;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018) and the use of social media during the pandemic (Cheung, 2021;Serhan, 2020;Suadi, 2021) in particular. Some learners believed that social media could help them develop their vocabulary knowledge (Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The data in Table 2 revealed that EFL learners have positive attitudes toward the use of social media in language learning, which is in line with the previous research with regard to the use of social media in general (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019;Bailey, Park, & Haji, 2017;Balbay, & Kilis, 2017;Eaton, 2010;Elia, 2006;Fewell, 2014;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018) and the use of social media during the pandemic (Cheung, 2021;Serhan, 2020;Suadi, 2021) in particular. Some learners believed that social media could help them develop their vocabulary knowledge (Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…In the EFL/ESL learning/teaching context, some researchers shed some light on different PSMs with regard to their uses, potentials, etc. including Instagram (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Anggraeni, 2017;Gonulal, 2019;Mansor, & Rahim, 2017;Sari, & Wahyudin, 2019), YouTube (Balbay, & Kilis, 2017;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018;Maziriri, Gapa, & Chuchu, 2020), Facebook (Atmaca, 2013;Bailey, Park, & Haji, 2017;Çakır, & Atmaca, 2015;Shukor , 2015;Terantino, 2013), Twitter (Cheng, 2012;Kim, Park, & Baek, 2017;Mompean, & Fouz-González, 2016;Said, & Abd Elfatah , 2015;Taskiran, Gumusoglu, & Aydin, 2018), Skype (Eaton, 2010, Elia, 2006Ockert, 2015Ockert, , 2020Yen, Hou, & Chang, 2015), Zoom (Cheung , 2021;Khusniyah, 2020;Nuryanto, 2021;Serhan, 2020), and What's App (Hamad, 2017;Noorani, & Salehi, 2019;Suadi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature reviews provide an insight into the language teachers' online experience. The authors would like to admit that there is not a country unaffected by the crisis (Amin, 2020;Asmara, 2020;Egbert, 2020;Cheung, 2021;Lesnichenko et al, 2020;Naqvi & Zehra, 2020;Okmawatti, 2020;Shevtsova & Kozubai, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The literature review provides coverage of the opinions and feedback on the forceful integration of online instruction (Amin, 2020;Asmara, 2020;Cheung, 2021;Kucheriv, 2020;Lesnichenko et al, 2020;Matvienko et al, 2020;Matvienko et al, 2021;Shevtsova & Kozubai, 2020;Sakalo, 2020;Zmievskaya et al, 2020). Distance learning is not a cutting-edge experience in many European, American, and Asian universities anymore.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation